Budaya Komunikasi Publik Kontemporer Analisis Strukturasi Komunikasi Publik Kementerian Komunikasi dan Informatika - Mochamad Taufiq Hidayat (PRoMEDIA, 2020)
AbstractThis article higlights government public communication as the prioritize for the public and citizens interests of government activities. Even there are no clear boundaries regarding the approach, tactics, process and benchmarks, yet to be define the successfull public communication activities. With the structuration approach, this study dissects the public communication approach the current framework of government communication institutional. The analysis was carried out in the institutional context of the Ministry of Communication and Information which legally has a formal role in government public relations communication. Readings on the culture of public communication show that the communication scope are an activities of information packaging also selective approaches to provide credible, fast-easily accessible information, developing synergies and information exchanges between institutions and the public. There is a culture gap of public communication forms because government own perspective in understanding the relationship between citizens and the state vis a vis government apparatus. In the future, there is a challenge for public relationspractitioners to create an environment of friendly public opinion (favorable).Keywords: Public communication, Communication culture, Government public relationsAbstraksiKomunikasi publik pemerintah menjadi sorotan, pasalnya aktivitas komunikasi kepada publik dan warga negara dinilai beberapa pihak belum mengedepankan kepentingan publik. Namun demikian, belum ada batasan yang jelas tentang pendekatan, taktik, proses dan tolok ukur keberhasilan aktvitas komunikasi publik. Dengan pendekatan strukturasi, studi ini membedah pendekatan komunikasi publik dalam kerangka kelembagaan komunikasi pemerintah saat ini. Analisis dilakukan dalam konteks kelembagaan Kementerian Komunikasi dan Informatika yang secara legal formal memiliki tugas dan peran dalam komunikasi kehumasan pemerintah. Pembacaan atas budaya komunikasi publik menunjukkan bahwa peran komunikasi mencakup pengemasan informasi, pendekatan selektif dalam penyediaan informasi yang kredibel, cepat dan mudah diakses, dan mengembangkan sinergi promosi pertukaran informasi antarlembaga dan masyarakat. Budaya komunikasi publik lebih dipengaruhi oleh cara pandang lembaga pemerintah dalam memahami hubungan antara warga negara dengan negara vis a vis aparatus pemerintah. Sementera, ke depan ada tantangan praktisi kehumasan pemerintah untuk bekerja menciptakan lingkungan opini publik yang bersahabat (favorable).Kata Kunci: Komunikasi publik, Budaya komunikasi, Kehumasan pemerintah